Macular morphology and response to ranibizumab treatment in patients with wet age-related macular degeneration - Dervenis N (Dove Medical Press, 2016)
Nikolaos Dervenis, Saad Younis Western Eye Hospital, Imperial College Healthcare NHS Trust, London, UK Purpose: The purpose of this study was to assess whether specific characteristics of spectral domain optical coherence tomography (SD-OCT) affect structural and functional outcomes and number of injections needed in ranibizumab (0.05 mL of 10 mg/mL Lucentis solution)-treated wet age-related macular degeneration (AMD) patients. Patients and methods: This retrospective case series included 62 newly diagnosed wet AMD patients treated with three monthly intravitreal ranibizumab injections followed by monthly follow-up and pro re nata retreatment. The presence of dome-shaped pigment epithelial detachment (PED), disruption of the retinal pigment epithelium (RPE), and subretinal and intraretinal fluid was associated with changes in Early Treatment of Diabetic Retinopathy Study visual acuity, central macular thickness (CMT), and number of injections needed during the 6-month follow-up. Results: The presence of PED was associated with lower values of CMT at presentation (399 µm [±132 µm] vs 310 µm [±51 µm], P=0.005). The presence of RPE disruption was associated with worse visual acuity in month 6 (0.36 [±0.22] vs 0.61 [0.45], P=0.027) and fewer injections (4.23 [±0.92] vs 3.55 [±0.60], P=0.007). The presence of intraretinal fluid at presentation was associated with worse visual acuity outcomes in month 4 (P=0.045) but not in month 6. Conclusion: The dome-shaped PED was associated with lower CMT at presentation, but it did not affect response to treatment. RPE disruption was associated with worse functional outcomes with fewer injections. Intraretinal fluid at presentation may suggest delayed response to treatment. Individualized SD-OCT analysis could lead to individualized approach to wet AMD patients. SD-OCT can offer imaging biomarkers to assess the prognosis of anti-VEGF treatment in AMD patients. Keywords: AMD, spectral domain optical coherence tomography, prognosis, anti-VEGF, ranibizumab